A Combined Cohesive Elements—XFEM Approach for Analyzing Crack Propagation in Bonded Joints. Issue 7 (1st September 2016) - Stuparu, F.; Constantinescu, D. M.; Apostol, D. A.; Sandu, M.
Abstract : Cohesive zone modelling (CZM) and extended finite element modelling (XFEM) available in Abaqus ® are used together to simulate the behavior and strength of a single lap adhesively bonded joint with an initial delamination in the adhesive. Depending on the thickness of the adhesive and the position of the initial delamination, the crack initiated and propagated by XFEM changes its trajectory following the principle of local symmetry reaching or not the interface. Meanwhile the failure of the interface between the adherent and the adhesive is initiated through CZM and crack propagation at the interface leads to the final failure of the single lap joint assembly. The two simulation models can be used successfully together.